Therapeutic Benefits of Miracle Tree Moringa oleifera: A Complete Overview - Shabnam, Faridi; Rani, Isha; Vivek, Dhiman; Goyal, Rajat; Kumar Gautam, Rupesh (Current Traditional Medicine, 2023)
Generally, Ayurvedic or herbal products are considered safe to use. According to a report, more than 50% of the global population depends upon herbal products. To meet the global demand for ayurvedic products, more and more herbal plants are analyzed for their active constituents and health benefits. Moringa oleifera is one such plant that is analyzed for its therapeutic benefits. Various parts of this plant, such as the leaves, roots, seed, bark, fruit, flowers, and immature pods, act as cardiac and circulatory stimulants with antipyretic, antitumor, anti-inflammatory, antiepileptic, diuretic, antiulcer, antispasmodic, antihypertensive, cholesterol-lowering, antidiabetic, antioxidant, antibacterial, hepatoprotective, and antifungal activities. This review is about the chemical composition of this tree’s market preparation and its different applications.
Keywords: miracle tree